Drivers of holding period firm-level returns in private equity-backed buyouts - Valkama, Petri; Maula, Markku; Nikoskelainen, Erkki; Wright, Mike (Journal of Banking & Finance, 2013)
We extend the research on the drivers of holding period firm-level returns in private equity (PE)-backed buyouts by examining deal-, industry-, and macroeconomic-level drivers and their interaction. To conduct our study, we use a comprehensive and hand-collected dataset covering exited buyouts in the UK between 1995–2004, and we control for sample selection and investment risk. Our study shows that governance variables generally have a limited role in driving value creation but that use of a ratchet is positively related to both equity and enterprise value returns; we also find that leverage has a positive impact on median and top-quartile equity returns. Moreover, returns are driven by the size of the buyout and the acquisitions made during the holding period. With respect to macroeconomic and industry level factors, industry growth particularly drives buyout returns. However, the effect of industry growth is not uniform; its influence is particularly strong in insider-driven and divisional buyouts, in addition to top-quartile transactions.